Are commercial ceilings appropriate for the regulation of commercial overload on free-to-air TV channels? - Julia Rothbauer; Gernot Sieg (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2014)
Commercial ceilings not only restrict broadcasters in their decisions about commercial broadcasting time, but also affect their differentiation of program content. This study examines the welfare effects of commercial ceilings in a two-sided free-to-air TV market, taking into account welfare with respect to content differentiation. We identify a second-best commercial ceiling that maximizes welfare in the absence of enforceable program content regulation and identify the situations in which laissez faire is optimal. The deregulation of commercial broadcasting can improve welfare, even if the laissez-faire level of commercial broadcasting time is excessive.
Keywords: L82; M38; D61; 330